Photon emission and changes in fluorescent properties of bone after laser irradiation. Issue 6 (22nd March 2021) - Sandri, Angela; Basso, Petra R.; Corridori, Ilaria; Protasoni, Marina; Segalla, Gabriel; Raspanti, Mario; Spinelli, Antonello E.; Boschi, Federico
Abstract: Laser scalpels used in medical surgery concentrate light energy, heating the tissues. Recently, we reported thermoluminescence emission from laser‐treated soft tissues. Here we investigated the thermo‐optical effects caused by a laser operating at 808 nm on animal bones (beef ribs) through luminescence and fluorescence imaging, thermal imaging and scanning electron microscopy. Laser‐induced artificial lesions emitted luminescence peaking around 650 nm, with a half‐life of almost 1 hour. As concerns fluorescence, 24 hours after laser treatment we observed an increase of the emission and a shift from 500 (untreated) to 580 nm (treated). Recrystallization observed by SEM indicates that the temperature in the artificial lesions is over 600°C. We can conclude that laser treatment induces specific luminescent and fluorescent emissions due to heating of the bone and modification of its components. Monitoring these emissions could help prevent tissue overheating and its potential damages during laser‐assisted medical procedures. Abstract : Laser scalpels commonly used in medical surgery concentrate light energy, heating the tissues. Due to heating and modification of tissue components, a surgical diode laser operating at 808 nm produced thermo‐optical effects on animal bones, such as specific emissions of luminescence and fluorescence. Monitoring these emissions could help prevent tissue overheating and its potential damages during laser‐assisted medical procedures.